Current state of production of аlternative energy on the Absheron Peninsula - Ramil Sadigov Ali; Nazila Alverdiyeva Farman; Gunay Mammadova Israphil; Vusala Isaqova Gudrat; Turkan Hasanova Allahverdi; Muhammad Madnee (International Journal of Applied Power Engineering (IJAPE), 2026)
The article is devoted to the study of the relationship between sustainable development and the introduction of innovative technologies, and the formation of smart cities. The Azerbaijan Republic is a land-poor country and has exhausted most of its natural resources. Therefore, the use of renewable energy sources and scientific research in this direction are important and topical issues for the country's scientists. Wind demand: in 10 months (from January to October) showed 3.000 GWh-4.000 GWh in Absheron (2020-2024 years). Since bioenergy can be produced in any weather, it is more reliable than solar and wind energy in Azerbaijan's regions. Seasonal variations in the availability of agricultural residues can lead to uneven energy production and create difficulties in ensuring a constant supply. The study is innovative given the importance of non-competition with food production, as well as the unique environmental, economic, and technological implications of each biofuel production method.